Chemical composition and nutritional value of Argentine commercial edible mushrooms - Di Anibal, Carolina Vanesa (2015)
The chemical composition and nutritional value of four edible mushroom varieties (Champignons, Portobellos, Girgolas and Shiitakes) commonly cultivated and consumed in Argentina was determined. Chemical composition includes water content, crude protein, lipids, ash, carbohydrates, mineral composition and bioactive components (dietary fiber, chitin content and phenolic compounds). Results show that edible mushrooms are rich sources of water and carbohydrates and have low amounts of lipids. Also, they are rich in potassium and phosphorus whereas have a low content of sodium. The composition of bioactive components reveals that mushrooms are rich in fiber and have an interesting amount of total phenolic compounds that could assure an antioxidant capacity. Chitin content is an important part of total fiber and in this work a new method for chitin isolation is proposed. Multivariate analysis (Principal Component Analysis) was applied to discriminate among the different mushrooms varieties and to establish relationships among samples and nutritional parameters.